2021
DOI: 10.1111/hiv.13189
|View full text |Cite
|
Sign up to set email alerts
|

Viral suppression after transition from nonnucleoside reverse transcriptase inhibitor‐ to dolutegravir‐based antiretroviral therapy: A prospective cohort study in Lesotho (DO‐REAL study)

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
(30 reference statements)
3
25
0
Order By: Relevance
“…Early outcomes (16 weeks) in this group were good (98% had viral load <100 copies per mL), with high suppression also among the few with viraemia at TLD initiation (95%). 26 It is highly encouraging that our results uphold and expand upon these earlier findings.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Early outcomes (16 weeks) in this group were good (98% had viral load <100 copies per mL), with high suppression also among the few with viraemia at TLD initiation (95%). 26 It is highly encouraging that our results uphold and expand upon these earlier findings.…”
Section: Discussionsupporting
confidence: 85%
“…‡Of 42 included, 36 were assessed at month 18, two were transferred out, three switched antiretroviral therapy following failure (two with dolutegravir drug resistance), and one lost to follow-up to the study (still in routine care). 25 To date, only one sub-Saharan African cohort (DO-REAL study) 26 reported on TLD transitioning with baseline viral load information. Early outcomes (16 weeks) in this group were good (98% had viral load <100 copies per mL), with high suppression also among the few with viraemia at TLD initiation (95%).…”
Section: Discussionmentioning
confidence: 99%
“… 1 Similarly, the DO-REAL study in Lesotho showed that among 44 participants with a VL above 100 copies/mL at transition, 42 (95%) dropped their VLs to below 100 copies/mL at follow-up. 14 These findings suggest that maintaining a tenofovir backbone rather than switching to zidovudine may be an appropriate option when switching to DTG-based therapy, allowing for continued 1 pill, once-a-day dosing and sparing the substantial adverse events associated with prolonged zidovudine therapy.…”
Section: Discussionmentioning
confidence: 89%
“…13 Similarly, a study in Lesotho showed that after switching to TLD, the proportion of participants with a VL , 100 copies/mL increased from 96% to 98%, and the percentage with pill count-based adherence .95% improved from 82% to 90%. 14 FIGURE 1. VL category by antiretroviral therapy switch status.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessing viral suppression in Lesotho after the initiative to transition to the use of TLD, revealed 98% suppression after regimen switch. 14 Thus, the generalizability of results from this study is limited to populations with similar prevalence of viral nonsuppression.…”
Section: Discussionmentioning
confidence: 97%